The Underground and Sky Diary - S. Blanchfield (Law Text Culture, 2008)
I spent a lot of time on and in the London Underground during June–September 2006 at all times of the day and night, marvelling at the density of people who use this system of transport every day and as a way of connecting with all the major London stations and airports that spread across the country and to Europe. It was impossible for me not to think of the bombings in July 2005 when on the tube and I was always thankful when I got off and emerged onto the streets again. One of the social rules is that you can’t make eye contact on the Underground too often, so I used to stare at the patterns on the seating upholstery and work out the repeat sequence to take my mind off the claustrophobic tunnels and crowds. There was a palpable tension in the carriages. The Paris Metro had a completely different feeling — much lighter and friendlier with the buskers moving from carriage to carriage. My other work, Sky Diary, includes the three days of cancelled and restricted flying in and out of London airports due to the foiled terrorist plot in August 2006.